RELIABILITY AND VALIDITY OF INSTRUMENT FOR ASSESSING CUSTOMERS’ SATISFACTION, TRUST AND PURCHASE INTENTION ON UMRAH TRAVEL AGENCIES WEBSITE FEATURES - Muhammad Saufi Anas; Hassnah Wee (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Online shopping has become a prominent consumer market in purchasing travel-related products and is likely to become the largest market in the future. Website quality and evaluation on the travel agency website features have generally been recognized as a critical step to drive business online because it will influence customers’ trust-building process and satisfaction level. There are a total of 274 travel agencies currently registered with the Ministry of Tourism and Culture (MOTAC) to provide the Umrah package in Malaysia. Due to a very competitive online travel package offers to Muslim pilgrimage for Umrah purpose, fraud packages have become a vital issue in the Malaysian market. Therefore, this study intends to develop an effective instrument to measure the Umrah Travel Agency website features based on customer satisfaction, trust, and the customers’ intention to purchase the Umrah package. Some essential website features identified from previous literature are outlined in this study, such as ease of use, visual appeal, information quality, and information relevancy. A quantitative method using a self-administered survey has been used to collect data from 100 local Muslim youths. The instruments’ validity, reliability, and normality of the data were analyzed by using SPSS software. The final result indicated that all 61 instruments in the questionnaire are reliable to be used in the actual study.